Harmonic analysis of cantilever beam with uniform cross section with a concentrated mass at its free end and with a uniformly distributed harmonic force. - Anuska Gautam; Nabin Adhikari; Mahesh Chandra Luitel (Journal of Innovations in Engineering Education, 2023)
Cracks are one of the most catastrophic breakdowns that reduce useful life and contribute to the collapse of structural elements and structures. Today, component failure is the primary cause of structural element and structure failure. Depending on the depth and location of the crack, surface cracks on structural elements like beams result in significant differences in stiffness of the component. Certain vibrational characteristics can be used to identify beam fractures. The existence of fractures affects vibration factors including mode shapes and natural frequencies as well as the structural integrity. Modal analysis may be used to determine vibrational properties including modal frequencies and mode shapes for a structural component. In this work, harmonic analysis of a cantilever steel beam is conducted for various scenarios with cracks, no cracks at various locations using ANSYS software. Harmonic analysis is done within the study by taking a uniformly distributed force over the beam and the change in modal frequencies along with change in deformation pattern for different cases are visualized.